UPAYA PENINGKATAN KEGIATAN SOSIAL DAN INTERAKSI SESAMA MAKHLUK HIDUP PADA MASYARAKAT DAN HEWAN DI KELURAHAN SETIABUDI - Angel Carveling; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2020)
In the era of globalization, capitalism, especially in urban areas is developing rapidly. The population is dominated by millennial. In the progression of the technology, people especially in urban areas become individualism, selfish and easily depressed. Relationships between humans and the environment are getting worst. One of the things that can rehabilitate human depression is interaction with animals. Interactions that occur between humans and animals can produce endorphins which make them happy when interacting. However, human and animal relations are increasingly damaged. Animals often be the victim from human selfishness and ignorance. The level of human concern for animals is diminishing. Humans and animals must coexist and help one another to protect the world's ecosystem. With narrative architectural methods, the sharing space